DEEP VEIN THROMBOSIS IN PELVIC AND FEMORAL FRACTURES IN EARTH QUAKE VICTIMS: Deep Vein Thrombosis in Earthquake Victims - Majeed, Nasim Ul; Shah, Mian Qaisar Ali; Malik, Sikandar Ali (Pakistan Armed Forces Medical Journal, 2006)
Objective: The aim of this prospective cum descriptive study was to determine the frequency of deep vein thrombosis using Duplex ultrasound scan, in a group of earth quake victims of 08 October, 2005. All these patients belonged to the high mountain northern areas of Pakistan and were admitted in Combined Military Hospital Rawalpindi with pelvic and/ or femoral fractures without additional risk factors for DVT. None of the patients had prior thromboprophylaxis. Place and Duration: Study was conducted in thirty female patients admitted in Family wing of Combined Military Hospital Rawalpindi from Oct 2005 to Feb 2006. Although we managed about 75 such cases, only 30 could be assessed for DVT by duplex ultrasound scan partly due to excessive work load on part of Ultrasound department but also because of early post operative mobilization of the patients as per policy, thus offering little chance of having positive results. Results: Out of thirty patients studied, DVT was found in 01(3.3%) patient, who belonged to Balakot and had pelvic fracture. Clinically she was asymptomatic and had no signs of DVT, but her duplex scan revealed calf veins involvement on the right side, with extension of the thrombus in to the femoral veins as well. Another patient with bilateral upper femoral fractures had painful swelling of both thighs, but her duplex scan for DVT was normal. Conclusion: The percentage of DVT observed in patients belonging to the northern areas is low in comparison to both our urban population research data as well the internationally conducted studies. Factors responsible might be dietary, racial or geographical, either alone or in combination, which need to be determined in focused, prolonged studies.